KESALAHAN BERBAHASA PADA PENULISAN PERSURATAN UKM MUSIK GAS 21 UIN RADEN MAS SAID SURAKARTA - Wahyu Adi Santoso; Nadhia Ana Zahraini; Oktavia Nirmalasari (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2021)
The purpose of writing in this study is to find out whether or not there are language errors in the GAS 21 Music UKM Letters at UIN Raden Mas Said Surakarta. UKM Musik GAS 21 is a student activity unit that oversees music and choir activities on campus. Not only that, UKM Musik GAS 21 has also participated and won competitions such as choirs, band festivals, etc., so in writing the correspondence must be true. It has been found that writing errors lie in linguistic errors in spelling and diction or inaccurate word choice. In this study using descriptive analytical method as a research method. The analytical descriptive method studied as a direct description of the linguistic errors studied, and its analytical by analyzing the linguistic errors in the student organization letter. Sources of data in this study are place permit letters, invitation letters to SMEs or other organizations, invitation letters to senior members of GAS 21, and other letters issued by GAS 21 in the administrative period of 2019/2020. It can be seen that the letter is a very important thing as a liaison, sign or invitation to the other party, and is to respect the other party, therefore the writing must be formal and in accordance with the rules of language.